A Facile High-Throughput Model of Surface-Independent Staphylococcus aureus Biofilms by Spontaneous Aggregation - Cheng, Terrence (mSphere, 2021)
Many microbes in their natural habitats are found in biofilm ecosystems attached to surfaces and not as free-floating (planktonic) organisms. Furthermore, it is estimated that nearly 80% of human infections are associated with biofilms. Biofilms are traditionally defined as three-dimensional, structured microbial communities that are attached to a surface and encased in a matrix of exopolymeric material. While this view of biofilm largely arises from in vitro studies under static or flow conditions, in vivo observations have indicated that this view of biofilms is essentially true only for foreign-body infections on catheters or implants where biofilms are attached to the biomaterial. In mucosal infections such as chronic wounds or cystic fibrosis or joint infections, biofilms can be found unattached to a surface and as three-dimensional aggregates. In this work, we describe a high-throughput model of aggregate biofilms of methicillin-resistant Staphylococcus aureus (MRSA) using 96-well plate hanging-drop technology. We show that MRSA forms surface-independent biofilms, distinct from surface-attached biofilms, that are rich in exopolymeric proteins, polysaccharides, and extracellular DNA (eDNA), express biofilm-related genes, and exhibit heightened antibiotic resistance. We also show that the surface-independent biofilms of clinical isolates of MRSA from cystic fibrosis and central catheter-related infections demonstrate morphological differences. Overall, our results show that biofilms can form by spontaneous aggregation without attachment to a surface, and this new in vitro system can model surface-independent biofilms that may more closely mimic the corresponding physiological niche during infection. IMPORTANCE The canonical model of biofilm formation begins with the attachment and growth of microbial cells on a surface. While these in vitro models reasonably mimic biofilms formed on foreign bodies such as catheters and implants, this is not the case for biofilms formed in cystic fibrosis and chronic wound infections, which appear to present as aggregates not attached to a surface. The hanging-drop model of biofilms of methicillin-resistant Staphylococcus aureus (MRSA), the major causative organism of skin and soft tissue infections, shows that these biofilms display morphological and antibiotic response patterns that are distinct from those of their surface-attached counterparts, and biofilm growth is consistent with their in vivo location. The simplicity and throughput of this model enable adoption to investigate other single or polymicrobial biofilms in a physiologically relevant setting.